2012
DOI: 10.1002/pca.2373
|View full text |Cite
|
Sign up to set email alerts
|

One‐step Preparative Separation of Two Polyhydroxystilbenes from Rheum likiangense Sam. by High‐speed Counter‐current Chromatography

Abstract: An optimised HSCCC method has been established for large-scale preparative separation of PHS compounds from Rheum likiangense Sam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Hence, simple and convenient methods have gained growing importance in the activity‐guided preparation separation for not only S . doederleinii , but also the other herbal medicines (Frighetto et al ., ; Wang et al ., ; Xian et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hence, simple and convenient methods have gained growing importance in the activity‐guided preparation separation for not only S . doederleinii , but also the other herbal medicines (Frighetto et al ., ; Wang et al ., ; Xian et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, the ingredients obtained from the herbal medicine studied are numerous, possibly causing aimlessness and time-consuming screening process for evaluation of their bioactivity. Hence, simple and convenient methods have gained growing importance in the activity-guided preparation separation for not only S. doederleinii, but also the other herbal medicines (Frighetto et al, 2005;Wang et al, 2012;Xian et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Modern pharmacology has demonstrated that rhubarb can cure constipation, hyperlipidaemia, hepatic injury and diabetes[ 2 5 ]. Chemical analysis shows that rhubarb contains anthraquinones, tannins, polyose, phenylbutazones, and stilbenes [ 6 9 ]. Relevant studies show that different active pharmaceutical ingredients (API) have different pharmacological activities, for example, emodin has effects in preventing viral infections, tumor, atherosclerosis, fungal infections and allergies [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature survey performed revealed over 50 publications that reported a sample loading of one or more grams, ,,,,, ,,, ,,,, as summarized in S4, Supporting Information. Ion-exchange methods have been shown to increase the loading capacity of CCS instruments.…”
Section: Optimization Of Ccs Operation Parametersmentioning
confidence: 99%